You are on page 1of 2

6.

𝑌" − 6𝑌′ + 9𝑌 = 𝑡𝑒 3𝑡 𝑌0 = 0 𝑌0 ′ = 5
𝐿(𝑌") − 6𝐿(𝑌′) + 9𝐿(𝑌) = 𝐿(𝑡𝑒 3𝑡 )
1!
𝑃2 𝑌 − 𝑃𝑌0 − 𝑌0′ − 6(𝑃𝑌 − 𝑌0 ) + 9𝑌 = (𝑃−3)1+1
1!
𝑃2 𝑌 − 𝑃𝑌0 − 𝑌0′ − 6𝑃𝑌 − 6𝑌0 + 9𝑌 = (𝑃−3)2
1!
𝑃2 𝑌 − 0 − 5 − 6𝑃𝑌 − 0 + 9𝑌 = (𝑃−3)2
1!
𝑃2 𝑌 − 5 − 6𝑃𝑌 + 9𝑌 = (𝑃−3)2
1
𝑃2 𝑌 − 6𝑃𝑌 + 9𝑌 = 5 + (𝑃−3)2
1
(𝑃2 − 6𝑃 + 9)𝑌 = 5 + (𝑃−3)2
1
(𝑃 − 3)2 𝑌 = 5 + (𝑃−3)2
5 1
𝑌 = (𝑃−3)2 + (𝑃−3)4
1 1
𝑌 = 5 (𝑃−3)2 + (𝑃−3)4
1
𝑌 = 5𝑡𝑒 −(−3𝑡) + 6 𝑡 3 𝑒 −(−3𝑡)
1
𝑌 = 5𝑡𝑒 3𝑡 + 6 𝑡 3 𝑒 3𝑡
13. 𝑦 ′′ + 𝑦 = 5 sinh 2𝑡 dengan 𝑦0 = 0, 𝑦0 ′ = 2

𝐿(𝑦 ′′ ) + 𝐿(𝑦) = 𝐿 (5 sinh 2𝑡) = 5𝐿(sinh 2𝑡)


2
𝑝2 𝑦 − 𝑝𝑦0 − 𝑦0 ′ + 𝑦 = 5. 𝑝2 −22

10
𝑝2 𝑦 + 𝑦 − 2 = 𝑝2 −4

10
𝑦(𝑝2 + 1) − 2 = 𝑝2 −4

10
𝑦(𝑝2 + 1) = +2
𝑝2 −4

10 2
𝑦 = (𝑝2 −4)(𝑝2 +1) + (𝑝2 +1)

1 1
𝑦 = 10𝐿−1 ((𝑝2 −4)(𝑝2+1)) + 2𝐿−1 ((𝑝2 +1))

1 1
𝑦 = 10𝐿−1 ((𝑝4 −4𝑝2 +𝑝2−4) + 2𝐿−1 ((𝑝2 +1))

1 1
𝑦 = 10𝐿−1 ((𝑝4 −3𝑝2 −4) + 2𝐿−1 ((𝑝2 +1))

1 1
𝑦 = 10 (− 5 sin 𝑡 + 10 sinh 2𝑡) + 2 sin 𝑡

𝑦 = −2 sin 𝑡 + sinh 2𝑡 + 2 sin 𝑡

𝑦 = sinh 2𝑡